Characteristics of Autonomic Activity and Reactivity During Rest and Emotional Processing and Their Clinical Correlations in Somatic Symptom Disorder. Issue 8 (October 2018) - Lee, Deokjong; Kim, Se Joo; Cheon, Jooah; Hwang, Eun Hee; Jung, Young-chul; Kang, Jee In
ABSTRACT: Objective: Altered autonomic nervous system activity is considered to be involved in the pathophysiology of somatic symptom disorder (SSD). This study aimed to investigate whether patients with SSD have disturbed autonomic activity during rest and reactivity to emotional processing and whether altered autonomic nervous system correlates with clinical characteristics and interoceptive accuracy in SSD. Methods: We recruited 23 patients with SSD and 20 healthy controls. Heart rate variability (HRV) was assessed during recording at rest and during performance of an emotional face dot-probe task. Alpha-amylase responses were also assessed. Patients with SSD completed a self-assessment survey and heart beat perception task, which reflects interoceptive awareness. Results: Patients with SSD had lower low-frequency HRV, high-frequency HRV, standard deviation of normal to normal R-R intervals (SDNN), and proportion of successive R-R intervals greater than 50 milliseconds (pNN50) at rest ( p < .05). The reactivity scores (during-task activity minus resting activity) for SDNN and pNN50 were significantly different between patients with SSD and controls (SDNN: p = .013; pNN50: p = .008). In addition, resting HRV parameters (low-frequency, high-frequency, SDNN, pNN50) correlated with heart beat perception error ( p < .01) in patients with SSD. No significant differences in α-amylase activity were found. Conclusions: Our findings showed that patients with SSD have altered resting-state autonomic activity and reactivity to emotional processing, and the resting-state autonomic activity correlated with their interoceptive awareness. These findings suggest that disturbed interactions between the autonomic nervous, affective, and interoceptive systems may be involved in the pathophysiology of SSD.